Analisis Strategi dan Metode Pembelajaran Akidah Akhlak - Maulana, Dias Maulana (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2025)
Strategies and methods in learning are the process of teaching and learning activities to achieve learning goals. In the learning process, there are reciprocal activities between teachers and students to achieve better goals. The learning process involves interaction between teachers and students as well as mutual communication that takes place in an educational situation to achieve learning goals. The approach in this study uses literature that analyzes strategies in the learning process between teachers and students, where the interaction between the two is two inseparable components. There is a mutually supportive interaction so that student learning outcomes can be achieved optimally. Strategies and methods carried out by teachers of moral beliefs can shape Islamic character in students.